Metabolic Alkalosis resulting from a Congenital Duodenal Diaphragm - Passariello, Annalisa; Maddalena, Ylenia; Malamisura, Monica; Rojo, Silvana; Aragione, Nunzia; Iaccarino, Emilia; Franco, Giuseppina; Giliberti, Paolo (Journal of Neonatal Surgery, 2014)
Duodenal diaphragm is an unusual cause of upper intestinal obstruction. We present here a neonate with duodenal diaphragm who presented with features of metabolic alkalosis. Further, an algorithm of management of metabolic alkalosis in a newborn is suggested.